- [-3 ... = + 3Remove all the grouping symbols. Simplify as you go by evaluating the numbers. Remove the brackets first.
a) 5−[3−(x−2)] =5−3+(x−2) =2+x−2 =x.
b) 5−[3−(x+2)] =5−3+(x+2) =2+x+2 =x+4.
c) −5+[3−(x−2)] =−5+3−(x−2) =−2−x+2 =−x.
d) 5−[−3−(x+2)] =5+3+(x+2) =8+x+2 =x+10.
I understand a,b & c
The rule as I understood it was if the sign before the grouping symbol is + then we remove the grouping symbol and do nothing. If the sign before the grouping symbol is - then we remove the grouping symbol and reverse the sign(s) that where within it. ie −5+3−(x−2) =−2−x+2.
But in D the first part is 5−[−3−(x+2)] =5+3+(x+2) whereas I work it as
5-[-3-(x+2)] = 5-3+(x+2) which is apparently incorrect.
Can somebody please advise me of my error?
I'm guessing it a sign rule that I forgot. Maybe its just too late and I should go to bed lol